2005
DOI: 10.1021/la0524216
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Mixed Langmuir Monolayers from Amphiphilic Block Copolymers and an Antimicrobial Peptide

Abstract: The behavior of binary monolayers from PMOXA-PDMS-PMOXA triblock copolymers and alamethicin, an antimicrobial peptide, was investigated in the context of formation of novel biocomposite nanostructured materials. The properties of mixed monolayers were studied by surface pressure-area isotherms and Brewster angle imaging. As reported previously, functionality of alamethicin relies on its aggregation properties in lipid mono-and bilayers. This is also the case in polymer matrixes, however, here the mixing proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 38 publications
9
73
0
Order By: Relevance
“…This value is in good agreement with the area for Alm molecule oriented with its helical axis parallel to the interface (S state). These results are consistent with the literature which reported that Alm is immiscible with phospholipids in monolayers spread at the air/water interface and the Alm molecules are oriented with axis of the helix parallel to the interface (3,31,32).…”
Section: Resultssupporting
confidence: 93%
“…This value is in good agreement with the area for Alm molecule oriented with its helical axis parallel to the interface (S state). These results are consistent with the literature which reported that Alm is immiscible with phospholipids in monolayers spread at the air/water interface and the Alm molecules are oriented with axis of the helix parallel to the interface (3,31,32).…”
Section: Resultssupporting
confidence: 93%
“…By varying the oligomer number and size it was shown that alamethicin forms voltage-dependent ion conducting pores [53]. The same behavior was observed when alamethicin was incorporated into a polymer membrane, which indicates that the polymer sufficiently mimics a lipid bilayer membrane, providing the essential environment for biopore insertion [30,54]. Alamethicin was also incorporated in a PMOXA 12 -PDMS 54 -PMOXA 12 tribolock copolymer membrane, as proved by the existence of multiple levels of conductance [55] (Figure 5).…”
Section: Biopores In Polymeric Membranementioning
confidence: 76%
“…A detailed phase behavior study was carried out by Haefele et al [54], showing the influence of alamethicin on the ABA triblock-copolymer membrane at an air-water interface ( Figure 6). Making use of the advantages of a copolymer membrane, in combination with the voltage-gated properties of alamethicin, holds great promise in terms of applying voltage-gated channels to targeted drug therapeutics.…”
Section: Biopores In Polymeric Membranementioning
confidence: 99%
“…Study of binary monolayers of PMOXA−PDMS− PMOXA triblock copolymers and alamethicin, a small amphiphilic antimicrobial peptide, indicated that the larger the polymer, the higher is its flexibility and ability to adopt conformations allowing host peptides in the membrane. [23] Both lipid-polythe protein-incorporated polymer membrane indicated a successful functional insertion of MloK1 (Fig. 5D).…”
Section: Functional Synthetic Membranes By Insertion Of Biomolecules mentioning
confidence: 87%